2008
DOI: 10.1093/carcin/bgn035
|View full text |Cite
|
Sign up to set email alerts
|

t10,c12-Conjugated linoleic acid stimulates mammary tumor progression in Her2/ErbB2 mice through activation of both proliferative and survival pathways

Abstract: The t10,c12 isomer of conjugated linoleic acid (CLA) inhibits rat mammary carcinogenesis, metastasis from a transplantable mouse mammary tumor and angiogenesis; however, it stimulates mammary tumorigenesis in transgenic mice overexpressing ErbB2 in the mammary epithelium (ErbB2 transgenic mice). In the current study, we report that a 4-week supplementation of the diet with 0.5% trans-10, cis-12 conjugated linoleic acid (t10,c12-CLA) stimulated the growth of established ErbB2-overexpressing mammary tumors by 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
6
16
1
Order By: Relevance
“…When we co-administered the IGF-1R inhibitor picropodophyllotoxin to OVX mice fed 10,12 CLA, ductal elongation was abrogated, indicating that activation of the IGF-1R was indeed necessary during this induction of MG growth. In support of these findings, phosphorylation of the IGF-1R/insulin receptor was increased in MG tumors from 10,12 CLA-fed mice overexpressing ErbB2 (Meng et al, 2008). …”
Section: A Case For Diet-induced E-independent Ductal Elongationsupporting
confidence: 52%
See 1 more Smart Citation
“…When we co-administered the IGF-1R inhibitor picropodophyllotoxin to OVX mice fed 10,12 CLA, ductal elongation was abrogated, indicating that activation of the IGF-1R was indeed necessary during this induction of MG growth. In support of these findings, phosphorylation of the IGF-1R/insulin receptor was increased in MG tumors from 10,12 CLA-fed mice overexpressing ErbB2 (Meng et al, 2008). …”
Section: A Case For Diet-induced E-independent Ductal Elongationsupporting
confidence: 52%
“…These changes include the increased local deposition of collagen (Russell et al, 2007), the recruitment of immune cells including macrophages and mast cells (Poirier et al, 2006; Russell et al, 2007; Shen et al, 2013), and an inflammatory state at both the systemic and tissue levels that manifests as decreased serum adiponectin (Purushotham et al, 2007) and elevated IL-6 and tumor necrosis factor-α mRNA in adipose tissue (Poirier et al, 2006; Shen et al, 2013). At the same time, the volume of the supramammary lymph nodes within the MG is increased by dietary 10,12 CLA, along with significant splenomegaly (Meng et al, 2008) and splenocyte proliferation (Hayek et al, 1999). The local inflammatory phenotype induced by dietary 10,12 CLA is also dose-dependent (Foote et al, 2010; Li et al, 2012; Shen et al, 2013).…”
Section: A Case For Diet-induced E-independent Ductal Elongationmentioning
confidence: 99%
“…In contrast, the 0.5% 10,12-CLA diet induced the emergence of buds along the entire ductal tree, and this morphological abnormality was associated with a doubling in the abundance of the marker of epithelial cell mass K18, suggesting increased proliferation. This is supported by increased Ki67 labeling in the TEB-like structures reported for the mammary glands of mature virgin mice consuming a 0.5% 10,12-CLA diet (27). The budding structures decorating the ducts in the 0.5% 10,12-CLA Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Despite abundant studies (reviewed in (Ip et al, 2003)) showing cancer protective effects of CLA in the rat mammary gland (a more relevant model for the human breast (reviewed in Medina and Thompson, 2000), studies in the mouse have shown different responses, both in normal stromal response (Russell et al, 2007;Tsuboyama-Kasaoka et al, 2000) as well as in limited effect on primary tumor growth (Hubbard et al, 2003(Hubbard et al, , 2006 or actual tumor stimulatory effects Meng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%